Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Yang Memperoleh Opini WTP Dengan Pemerintah Daerah Yang Memperoleh Opini Non WTP - Riki Kurnia; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2019)
The research aims to find out: empirical evidence of financial performance comparisons of District/city governments with unexempted fair opinions (WTP) and non WTP based financial performance ratios in West Sumatera province in 2015-2017. Selection of samples using purposive sampling method. The regional government's financial performance is measured by the ratio of regional financial independence, effectiveness ratio, efficiency ratio, operating expenditure ratio, capital expenditure ratio and growth ratio compared between local governments that have WTP and non WTP opinions are obtained through the financial statement of the Local government (LKPD) which has been audited by the Financial Audit Board of BPK. Hypothesis testing using different independent T-Test tests. The results of this research proved that there is a difference in financial performance from various financial ratios between the city/District government that obtained WTP and non WTP opinions, with the results thitung 2,207 >This 2.003 a significant value of 0.103>0.05. And there are differences in financial performance criteria of efficiency, effectiveness, shopping operations, capital expenditure and growth of PAD between the city/District government that obtained the opinion WTP and non WTP.